1985
DOI: 10.1111/j.1365-2427.1985.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding efficiencies of Chironomus plumosus (L.) and C. anthracinus Zett. (Diptera: Chironomidae) in mesotrophic Lake Erken

Abstract: Absorption efficiencies of nitrogen and carbon in twoChironomus species found dominating in the profundal zone of mesotrophic Lake Erken were determined gravimetrically.2. Absorption efficiencies for C. plumosus showed greater seasonal variation than those of C. anthracinus, with low efficiencies coinciding with the summer dominance of flagellate phytoplankton and with high C:N ratios.3. Overall mean absorption efficiencies {±SE) for carbon and nitrogen, respectively, were 26.8% (±1.9) and 29.3% (±1.9) for C p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…These larvae exhibit a flexible feeding mode, switching between deposit-and filterfeeding, depending on food availability (McLachlan 1977, Johnson 1985, Berg 1995, Goedkoop et al 1998). Thus, they could feed on microbial biomass from the sediment as well as from the water directly above the sediment surface, a region in which in many lakes oxic/anoxic interfaces occur, providing the preferred habitat for MOB (Hanson & Hanson 1996).…”
Section: Abstract: Food Web · Chironomid Larvae · Symbionts · Methanmentioning
confidence: 99%
“…These larvae exhibit a flexible feeding mode, switching between deposit-and filterfeeding, depending on food availability (McLachlan 1977, Johnson 1985, Berg 1995, Goedkoop et al 1998). Thus, they could feed on microbial biomass from the sediment as well as from the water directly above the sediment surface, a region in which in many lakes oxic/anoxic interfaces occur, providing the preferred habitat for MOB (Hanson & Hanson 1996).…”
Section: Abstract: Food Web · Chironomid Larvae · Symbionts · Methanmentioning
confidence: 99%
“…1, an interesting continuum from lake profundal to reservoir profundal to reservoir littoral to natural pools is obvious for Chironomus species and their ecology. The filter-feeding Chironomus plumosus dominates the lake profundal zone (McLACHLAN and CANTRELL, 1976) and gives way to the deposit-feeding Chironomus anthracinus in the reservoir profundal zone (JOHNSON, 1985). Chironomus aberratusgroup larvae co-occur with C. anthracinus and become common species in the shallow organic littoral in these reservoirs.…”
Section: Prnfundal Fauna As Environmental Indicatormentioning
confidence: 99%
“…In 1992, C. plumosus pupae were not found in Ekmann-Birge samples during this period, but exuviae exhibiting the emergence of adult midges were collected from the sediment. In 1982In , 1983In , 1984In , 1985In , 1986In and 1991, a second emergence period was not clearly observed.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Several investigators have reported the importance of newly deposited organic matter at the sediment surface in the diet of C. plumosus larvae (e.g., JOHNSON, 1985JOHNSON, , 1989. Therefore, chl-a concentrations at 6 m depth do not necessarily reflect the amount of available food resources for C. plumosus.…”
Section: Environmental Factorsmentioning
confidence: 99%